Local stochastics and ecoclimatic situation shape phytophagous chafer assemblage composition - U. G. Sasanka L. Ranasinghe; Jonas Eberle; Suresh P. Benjamin; Dirk Ahrens (Ecology and Evolution, 2023)
Abstract Very little is known about factors determining the assemblage structure of megadiverse polyphagous‐herbivore scarab chafers in the tropics (Coleoptera: Scarabaeidae). Here, we examined the composition of Sri Lankan chafer assemblages and investigated whether it is influenced more by the general ecoclimatic situation, macrohabitat, or indetermined stochastic biotic and abiotic factors of each locality. We also explored the influence of the latter on separate lineages and general body size. Based on dedicated field surveys conducted during the dry and wet seasons, we examined 4847 chafer individuals of 105 species sampled using multiple UV‐light traps in 11 localities covering different forest types and altitudinal zones. Assemblages were assessed for compositional similarity, species diversity, and abundance within four major eco‐spatial partitions: forest types, elevational zones, localities, and macrohabitats. Our results revealed that assemblages were shaped mainly by locality stochastics (i.e., multi‐factor ensemble of all biotic and abiotic environmental conditions at local scale), and to a minor extent by ecoclimatic conditions. Macrohabitat had little effect on the assemblage composition. This was true for the entire chafer assemblage as well as for all single lineages or different body size classes. However, in medium and large species the contrasts between localities were less pronounced, which was not the case for individual lineages of the assemblage. Contrasts of assemblage similarity between localities were much more evident than those for forest types and elevation zones. Significant correlation between species composition and geographic distance was found only for the assemblage of small‐bodied specimens. Seasonal change (dry–wet) in species composition was minor and only measurable in a few localities. The strong turnover between examined localities corroborates with the high degree of endemism in many phytophagous chafers, particularly in Sericini. Connected with their hypothetic poor habitat specificity and polyphagy, this might also explain why so many chafer crop pests in the Asian tropics are endemics.